Integration of Islamic Religious Education and Mathematics in Digital Learning to Form the Character of the Society 5.0 Generation (International Forum of Researchers and Lecturers, 2025)
This study examines the integration of Islamic Religious Education and Mathematics within a digital learning environment and its potential role in shaping students' character in the context of Society 5.0. The study employs the Systematic Literature Review (SLR) method to analyze existing studies on the integration of these two subjects through digital learning platforms. The results of the literature review reveal various models of integration, highlighting the role of technology in facilitating the merging of religious education with mathematical thinking. Additionally, this study evaluates the impact of this integration on the development of students' moral and ethical values, as well as the enhancement of their critical, logical, and creative thinking skills. The findings suggest that the integration of Islamic Religious Education and Mathematics not only improves academic learning but also plays a crucial role in character building, fostering values such as responsibility, honesty, and respect. Despite its great potential, this integration faces challenges such as limited technological infrastructure and teacher readiness. This research provides insights into the practical implications of this integration in educational practice in the digital era.